To multiply the polynomials \((2x−7)(3x^2+7x−8)\), we will use the distributive property.
-
Distributing \(2x\) to each term in \(3x^2 + 7x - 8\):
- \(2x \cdot 3x^2 = 6x^3\)
- \(2x \cdot 7x = 14x^2\)
- \(2x \cdot -8 = -16x\)
-
Distributing \(-7\) to each term in \(3x^2 + 7x - 8\):
- \(-7 \cdot 3x^2 = -21x^2\)
- \(-7 \cdot 7x = -49x\)
- \(-7 \cdot -8 = 56\)
Now, let's combine all the results: \[ 6x^3 + 14x^2 - 16x - 21x^2 - 49x + 56 \]
Next, combine like terms:
- For \(x^2\): \(14x^2 - 21x^2 = -7x^2\)
- For \(x\): \(-16x - 49x = -65x\)
The resulting polynomial is: \[ 6x^3 - 7x^2 - 65x + 56 \]
Now, we can identify the coefficients:
- The coefficient of \(x^3\) is \(6\).
- The coefficient of \(x^2\) is \(-7\).
- The coefficient of \(x\) is \(-65\).
- The coefficient of the constant term is \(56\).
So, the values for the response areas are:
- The value of the coefficient of the \(x^3\) is 6.
- The value of the coefficient of the \(x^2\) is -7.
- The value of the coefficient of the \(x\) is -65.
- The value of the coefficient of the constant is 56.